2012
DOI: 10.1590/s0102-311x2012001100015
|View full text |Cite
|
Sign up to set email alerts
|

Lazer sedentário e consumo de alimentos entre adolescentes brasileiros: Pesquisa Nacional de Saúde do Escolar (PeNSE), 2009

Abstract: The objective of this paper was to investigate whether sedentary leisure time was associated with increased regular consumption of unhealthy foods, independently of socio-demographic indicators and family context. The analysis included 59,809 students from the Brazilian National School-Based Adolescent Health Survey (PeNSE) in 2009. The response variable was sedentary leisure time, defined as watching more than two hours of TV daily. The target explanatory variables were regular consumption of soft drinks, swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 34 publications
(38 reference statements)
4
27
1
14
Order By: Relevance
“…Moreover, a study that used data from PeNSE 2012 showed a poorer quality diet among girls compared with boys 30 , suggesting that Brazilian female adolescents are more exposed to inadequate food consumption 29,30 . The finding regarding the association gradient between a higher amount of time spent watching TV and more elevated consumption of sugar-rich food products among adolescents is also consistent with evidence from other studies 17,31,32,33,34 . Evidence suggests that behavioral risk factors, such as the habit of watching TV, or lengthy screen time, and inadequate food consumption, have an influence on one another, tending to coexist in the form of a cluster, resulting in added risk of the development of overweight and comorbidities 32 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, a study that used data from PeNSE 2012 showed a poorer quality diet among girls compared with boys 30 , suggesting that Brazilian female adolescents are more exposed to inadequate food consumption 29,30 . The finding regarding the association gradient between a higher amount of time spent watching TV and more elevated consumption of sugar-rich food products among adolescents is also consistent with evidence from other studies 17,31,32,33,34 . Evidence suggests that behavioral risk factors, such as the habit of watching TV, or lengthy screen time, and inadequate food consumption, have an influence on one another, tending to coexist in the form of a cluster, resulting in added risk of the development of overweight and comorbidities 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Evidence suggests that behavioral risk factors, such as the habit of watching TV, or lengthy screen time, and inadequate food consumption, have an influence on one another, tending to coexist in the form of a cluster, resulting in added risk of the development of overweight and comorbidities 32 . This coexistence can be justified by the elevated exposure of adolescents with higher screen time to advertisements of food products with elevated calorie content, such as sweets and soft drinks, favoring the consumption of those food groups instead of products with less media exposure, such as fruits and vegetables 14,17,31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porém, poucos estudos analisaram essa relação com vistas, especialmente, ao consumo alimentar de adultos em países em desenvolvimento 42 . No Brasil, a maioria dos estudos realizados é dedicada a avaliar essas relações apenas em crianças ou adolescentes 43,44 , ou restringem sua abordagem à análise da associação entre o hábito de assistir à TV e a prática de atividade física 45,46 .…”
Section: -2011unclassified